2016
DOI: 10.1002/mus.25068
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of myasthenia gravis in Northern Portugal: Frequency estimates and clinical epidemiological distribution of cases

Abstract: These figures are in keeping with similar studies and emphasize the importance of diagnosis and management of MG in elderly populations. Muscle Nerve 54: 413-421, 2016.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
17
2
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 39 publications
3
17
2
4
Order By: Relevance
“…Our results revealed an average MG mortality rate of 1.76 per 1 million population for both sexes combined, which is higher than previously reported mortality rates in other countries . In a systematic review of 8 epidemiological MG studies, reported mortality rates ranged from 0.06 to 0.89 per 1 million population per year .…”
Section: Discussioncontrasting
confidence: 65%
See 2 more Smart Citations
“…Our results revealed an average MG mortality rate of 1.76 per 1 million population for both sexes combined, which is higher than previously reported mortality rates in other countries . In a systematic review of 8 epidemiological MG studies, reported mortality rates ranged from 0.06 to 0.89 per 1 million population per year .…”
Section: Discussioncontrasting
confidence: 65%
“…6 Another study from the same country found the highest mortality rate ratio in women with late-onset MG compared with individuals from the general population. 26 This could be explained by a significantly older age at onset in women with MG in their cohort and possible higher frequency of comorbidities. This previous study included only patients with MG who were seropositive.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The estimated annual incidence is 1–2 per 100,000 and the prevalence is as high as 20–50 per 100,000 (2, 3). Recent epidemiological studies indicate that, like other autoimmune diseases, its incidence is rising considerably (4).…”
Section: Introductionmentioning
confidence: 99%
“…The disease is rare; the estimated annual incidence is 1-2 per 100,000, and the prevalence ranges from approximately 7-20 per 100,000, according to regional studies performed since 1990. [3][4][5] Recent epidemiological investigations have indicated that, similarly to other autoimmune diseases, the incidence of MG is rising considerably. 6 Such increases can be partially attributed to improved diagnostic precision and rising longevity of the populace, but a genuine rise in incidence may indicate the important role of environmental contributions.…”
mentioning
confidence: 99%